PROSPECTS OF INCREASING EXPORT AUTHORITY IN THE DEVELOPMENT OF THE REGIONAL ECONOMIC SYSTEM (Marketing Journal, 2025)
The article provides a scientific and empirical analysis of the prospects for enhancing export potential in the development of the regional economic system , using Surkhandarya region as a case study . The research assesses the relationship between export volume , export intensity , qualitative characteristics of export structure , as well as logistical and institutional factors , and the dynamics of regional economic growth , employment , and income . Based on statistical data for the period 2017 –2023, a comparative analysis of the impact of export potential on regional development across territories is conducted . The results indicate that the consistent development of export potential supports economic activity and sustainable growth , while diversification of export structure and an increase in the share of high value -added products are of particular importance . The findings have practical relevance for improving regional export policy .
Keywords: regional economy; export potential; export prospects; regional development; economic diversification; high value added; industrial clusters; competitiveness; institutional environment; sustainable development; global value chains; logistics infrastructure; innovative exports